Pengaruh Energi Input Micro-Plasma Arc Welding Terhadap Struktur Mikro dan Sifat Mekanik Sambungan Baja DIN 2311 - Yota, Richard Shan; Basuki, Widodo Widjaja; Manalu, Ferry Rippun Gideon; Widiarto, Sandra Octaviani B. (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2025)
Molds are important components in the plastic injection molding processes. Even though molds are generally made of strong and heat-resistant steel, but when used repeatedly and continuously, the mold will also experience damage such as scratches and dents caused by dynamic thermal and mechanical loading. Making new molds requires very high costs. Mold repairs using traditional welding such as laser welding and Tungsten Inert Gas welding, apart from requiring relatively high costs, also require sophisticated skills. This problem can be overcome with Micro-Plasma Arc Welding (MPAW). With this welding method, the process of melting the material and filler is concentrated at one point which prevents the spread of excess heat to the parent material. Welding on DIN 2311 low alloy steel, which is often chosen as a plastic molding material, was carried out with weld energies of 120, 132 and 144 J. The welding results were tested to determine the microstructure evolution, hardness distribution and strength values ​​of each specimen. From the test results of materials processed through MPAW, it can be concluded that the specimen produced with a weld energy of 132 J has the most optimal microstructure and hardness distribution so that it can have strength equivalent to the strength of the original material before welding, with relatively high ductility as proven by its ability to perform plastic deformation of 7.8% or just 3.2% lower than the ability of the original material.